(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This study examines methods and strategies for optimizing fuel consumption in thermal power plants, with the aim of identifying the most effective approaches to achieving measurable fuel savings without compromising power output. Thermal power generation remains the dominant source of electricity worldwide, yet its inherent thermodynamic inefficiencies result in substantial fuel waste and elevated operating costs. Employing a comparative analytical methodology, this research evaluates five principal fuel-saving strategies: combustion optimization, waste heat recovery, steam cycle improvement, auxiliary power reduction, and load management, using operational data from gas-fired and coal-fired power stations. Results demonstrate that integrated implementation of these strategies can achieve cumulative fuel savings of 8-15%, corresponding to significant reductions in both operating costs and environmental impact. The findings provide a practical framework for power plant operators and energy policymakers seeking to enhance the fuel efficiency of existing thermal generation assets.